Religious Specificities in the Early Sultanate of Banten (Western Java, Indonesia) - Gabriel Facal (JURNAL INDO-ISLAMIKA, 2014)
The author examines the religious specifics of Banten during the early Islamizing of the region. The main characteristics of the process resided in a link between commerce and Muslim networks, a strong cosmopolitism, a variety of the Islam practices, the large number of brotherhood followers and the popularity of esoteric practices. These specificities indicated that the Islamizing of the region was very progressive within 16th century and the processes of conversion also generated inter-influence with local religious practices and cosmologies. As a consequence, the widespread assertion that Banten is a bastion of religious orthodoxy and the image the region suffers today as hosting bases of rigorist movements may be nuanced by the variety of the forms that Islam took throughout history. The dominant media-centered perspective also eludes the fact that tide connection between religion and ritual initiation still composes the authority structure. This article aims to contribute to the knowledge of the religious aspects in the Bantenese society.